Bending strength and reliability of porcelains used in all-ceramic dental restorations - De Almeida, A. A. [UNESP]; Adabo, G. L. [UNESP]; Galvão, B. R. [UNESP]; Longhini, D. [UNESP]; Simba, B. G. [UNESP]; Dos Santos, C. (FapUNIFESP (SciELO), 2018)
Four dental porcelains for covering zirconia were sintered (fired) at 910-960 °C and characterized, focusing in analyzing reliability, physical and mechanical properties. Samples with relative density close to 99% presented leucite crystallization apart from residual amorphous phase. Hardness between 491±23 and 575±32 HV was different among all ceramics. Fracture toughness between 1.13±0.11 and 1.42±0.25 MPa.m1/2 was statistically different. Bending strength results were not different for three porcelain groups (73±9 to 75±12 MPa), with the exception of one specific group (62±4 MPa). Weibull analysis indicated bending strength between 73 and 75 MPa, Weibull modulus (m) between 5.7 and 7.1, while the ceramic with strength of 60 MPa presented m=13.6. The use of classical theory of fracture mechanics associated to the results of properties obtained in this work indicated the critical failure size in these ceramics lays between 65 and 90 μm and the theoretical fracture energy of porcelains is approximately from 10.5 to 16.3 J/m. It was concluded that the porcelains had different behavior, and it seems that there is no clear relationship among the studied properties.
Keywords: Fixed dental prostheses (FDPs); Mechanical properties; Metal-free systems; Veneering ceramics